2012
DOI: 10.5539/ies.v5n6p177
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Algebraic Solving Ability: A Theoretical Framework

Abstract: Algebraic solving ability had been discussed by many educators and researchers. There exists no definite definition for algebraic solving ability as it can be viewed from different perspectives. In this paper, the nature of algebraic solving ability in terms of algebraic processes that demonstrate the ability in solving algebraic problem is discussed. A theoretical framework of algebraic solving ability was formulated based on three phases of algebraic processes, historical development of algebra and SOLO mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
1
9
0
6
Order By: Relevance
“…In the answers at the level of uni-structural thinking, it was determined that they proposed only the social distance (two meters) should be written all over the figure, and the resulting shape was not evaluated multi-structural. As a matter of fact, this situation is parallel to the results obtained from some studies (Jurdak, 1991;Lian & Yew, 2012). In the study where Jurdak (1991) showed the relationship between SOLO taxonomy levels and Van Hiele levels, it was stated that the visual level, which is the beginning of Van Hiele geometric thinking levels, was the uni-structural level in the SOLO taxonomy.…”
Section: Discussionsupporting
confidence: 62%
“…In the answers at the level of uni-structural thinking, it was determined that they proposed only the social distance (two meters) should be written all over the figure, and the resulting shape was not evaluated multi-structural. As a matter of fact, this situation is parallel to the results obtained from some studies (Jurdak, 1991;Lian & Yew, 2012). In the study where Jurdak (1991) showed the relationship between SOLO taxonomy levels and Van Hiele levels, it was stated that the visual level, which is the beginning of Van Hiele geometric thinking levels, was the uni-structural level in the SOLO taxonomy.…”
Section: Discussionsupporting
confidence: 62%
“…This is corresponding with the statement of Lian & Idris (2006) that students at the extended abstract level can expand the application of information provided in new situations. In line with this statement, Lian & Yew (2012) stated that students at the extended abstract level can apply all aspects of the data to other situations. Braband & Dahl (2008) also provided a statement that students at this level can use their ideas in new situations.…”
Section: Students' Responses Leveling Withmentioning
confidence: 93%
“…For others too, the primary cause of many learners committing implementation errors is a lack of mathematical knowledge [15,31]. A potential solution offered is that in the process of conflicts between new knowledge and existing knowledge the logic is to wait for restructured schema to accept or connect in order to work and produce correct solutions and hence the need for the current study [22,25]. Thus, the errors and misconceptions will only be corrected if learners are able to revise old concepts before learning a new concept.…”
Section: Related Work and Development Of Research Questionmentioning
confidence: 99%